WEAKNESSES OF VSTEP-LIKE ARGUMENTATIVE ESSAYS BY SECOND-YEAR MAINSTREAM STUDENTS IN FELTE, ULIS, VNU = ĐIỂM YẾU CỦA NHỮNG BÀI VĂN NGHỊ LUẬN THEO ĐỊNH DẠNG VSTEP VIẾT BỞI SINH VIÊN NĂM HAI HỆ ĐÀO TẠO CHUẨN KHOA SƯ PHẠM TIẾNG ANH - Lê, Diệu Linh (2020)
From a long time, argumentative writing has been proved to be of fundamental importance to university students. For second-year students in ULIS, VNU, argumentative writing seems to be more important as it is also one of the genres tested in the VSTEP exam. However, many of students still encountered great difficulties with this genre, which is one factor leading to their reluctance to take the test. This study was conducted with an aim to investigating the most frequent problems in students’ VSTEP-like argumentative essays and thus, getting them ready for the writing part in the VSTEP exam. The participants are 36 mainstream students of QH.2015. They did the questionnaire first and then wrote the essays in 40 minutes. While questionnaire was used to find out students’ perceptions about their weaknesses in four aspects, namely Task Fulfillment, Organization, Vocabulary and Grammar, writing test was used to evaluate their actual competence and detect their weaknesses. To ensure the reliability of the results, two VSTEP-trained raters were asked to mark 36 essays separately and point out the problems. The questionnaire reveals that the weakest area perceived by students was Vocabulary and four problems that troubled them the most were “developing ideas”, “not smooth transitions of ideas”, “using mainly common words” and “making grammar/ punctuation mistakes”. The marking, on the other hand, shows that students’ weakest area was Organization and detects two new problems which are “using unclear reference” and “having unclear expressions”. It is also noted that students’ score marked by raters was higher than the score they perceived and there existed quite a few gaps between students’ perceived weaknesses and their actual ones.